2021
DOI: 10.1016/j.esmoop.2021.100075
|View full text |Cite
|
Sign up to set email alerts
|

The DNA damage response network in the treatment of head and neck squamous cell carcinoma

Abstract: Background: We sought to determine whether DNA damage response (DDR)-related aberrations predict therapeutic benefit in cisplatin-treated head and neck squamous cell carcinoma (HNSCC) patients and how DDR pathways are modulated after treatment with olaparib alone or in combination with cisplatin or durvalumab. Patients and methods: Oxidative stress, abasic sites and DDR-related parameters, including endogenous DNA damage, DNA repair mechanisms and apoptosis rates, were evaluated in HNSCC cell lines and periphe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 83 publications
0
17
0
Order By: Relevance
“…Genes involved in the UPR and UV response are vital for maintaining proteostasis and genome stability ( Mansilla et al, 2013 ; Strozyk and Kulms, 2013 ; Wang et al, 2019 ; Zhang et al, 2020 ). Previous evidence has functionally implicated these homeostatic mechanisms in HNSCC by regulating key tumor biology processes including cancer cell survival and therapy resistance, while their activities have also been associated with HNSCC prognosis ( Pluquet and Galmiche, 2019 ; Psyrri et al, 2021 ). Furthermore, by overlapping the genes in these three pathways across different cohorts, we identified 101 core genes that were able to subgroup the patients with distinct survival outcomes and molecular profiles.…”
Section: Discussionmentioning
confidence: 99%
“…Genes involved in the UPR and UV response are vital for maintaining proteostasis and genome stability ( Mansilla et al, 2013 ; Strozyk and Kulms, 2013 ; Wang et al, 2019 ; Zhang et al, 2020 ). Previous evidence has functionally implicated these homeostatic mechanisms in HNSCC by regulating key tumor biology processes including cancer cell survival and therapy resistance, while their activities have also been associated with HNSCC prognosis ( Pluquet and Galmiche, 2019 ; Psyrri et al, 2021 ). Furthermore, by overlapping the genes in these three pathways across different cohorts, we identified 101 core genes that were able to subgroup the patients with distinct survival outcomes and molecular profiles.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies revealed polymorphisms of DDR genes as potential risk factors that promote head and neck cancer progression. Altered expression levels of DNA repair genes, including both upregulation and downregulation, have been shown in oral cancer studies (Wang et al, 2007;Jenkins et al, 20132013;Ali et al, 2017;Dylawerska et al, 2017;Psyrri et al, 2021). Thus, detailed functional studies are necessary to further elucidate how these DDR alterations impact the progression and treatment responses of oral cancer.…”
Section: Acquired Cancer Resistance In Oral Cancer Is Associated With Altered Ddr Pathwaysmentioning
confidence: 99%
“…DNA damage response pathways are activated following endogenous and exogenous damage of DNA [179]. Poly (ADP-ribose) polymerase 1 (PARP1) is a member of poly (ADP) ribose moiety enzyme superfamily which repairs single-strand and double-strand breaks [180].…”
Section: Dna Repair Pathwaymentioning
confidence: 99%
“…Moreover, increasing evidence from trials in solid tumours suggests that DNA damage repair (DDR) alterations may predict response to immunotherapy [184]. Recently Psyrri et al, showed that changes in DDR signals are implicated in the response to HNSCC chemotherapy and can be exploited as novel therapeutic targets and sensitive/effective non-invasive biomarkers [179]. A Phase I trial of olaparib at 25 mg orally twice daily with concurrent cetuximab and radiation for heavy smoker patients with locally advanced HNC was well tolerated with reduced dermatitis within the radiation field.…”
Section: Dna Repair Pathwaymentioning
confidence: 99%